The Role of Teachers in Building Self-Confidence among Students from Low-Income Family Backgrounds at MIS Raudhatul Jannah - Dedi Sahputra Napitupulu; Tarmiji Siregar; Mariana Haenuri (Yayasan Adra Karima Hubbi, 2026)
Background. Students from low-income family backgrounds frequently face psychological challenges, including diminished self-confidence, that can hinder their full participation in the educational process. This condition demands specific and empathetic strategies from teachers to ensure that students remain able to develop optimally despite their socioeconomic limitations. Purpose. Purpose. This study aims to describe the role of teachers in building the self-confidence of students from low-income family backgrounds at MIS Raudhatul Jannah. Method. This study uses a qualitative field research approach. Data were collected through participatory observation, in-depth interviews with teachers, the school principal, students, and parents, and documentation analysis. Data were analyzed using interactive analysis techniques involving data reduction, data display, and conclusion drawing, and validity was ensured through source, technique, and time triangulation.. Results. Findings reveal that teachers play a highly significant role in strengthening students' self-confidence through three primary strategies: providing appropriate and process-focused appreciation, involving students in leadership roles and activities, and cultivating a positive mindset through language intervention and visual media Conclusion. Teachers function not only as instructors but also as the primary source of motivation and psychological support. The active role of teachers is essential in creating a learning environment that supports the psychological development of students, especially those from low-income families.